Penggunaan Tepung Buah Pepaya Carica papaya L Dalam Pelet Terhadap Efek Pertumbuhan Benih Ikan Nila Oreochromis niloticus - Tulung, Herol A.; Lumenta, Cyska; Ngangi, Edwin L.A. (e-Journal BUDIDAYA PERAIRAN, 2018)
This study aimed to determine the effect of papaya flour at different doses on absolute  growth, daily growth, relative growth, feed efficiency, and food conversion. The treatments consisted of 0,  2.5%, 7.5%, 10% of papaya flour respectively, each with three replcations. The weight of fish were  about 18-23.58 g.  The fish were placed in aquaria with a density of  10 individual per aquarium. The experiment design is a complete randomized design. The results of analysis show that the treatments had no significant effect on growth, daily growth, relative growth, feed  efficient, and food conversion ratio. However, treatment C (7.5% papaya flour) gave the best on growth of fish, feed efficiency and food conversion ratio.